Share Investors’ Competence and Overconfidence in Investment Decision Making - Kusnandar, Deasy Lestary; Rosyadi, Agi; Rinandiyana, Lucky Radi (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2019)
Many factors may affect investors in making investment decision, some of them are overconfidence and competence. Those factors thought to have an influence on investment decision making. This research objectives to determine the effect of competence and overconfidence on investment decision. This research is a kind of quantitative research using survey method given to beginner investor. The sampling method used judgment sampling with the number of samples in this research are 30 respondents of beginner investor. The analysis used is MRA (Multiple Regression Analysis). The results of this study showed that competence of investor does not affect in investment decision while investor’s decision was influenced by overconfidence of investor. Keywords : competence, overconfidence. investment decision